A comprehensive review of robotics-aided aircraft non-destructive inspection towards the smart hangar - Plastropoulos, Angelos; Zolotas, Argyrios; Avdelidis, Nicolas P. (Cambridge University Press (CUP), 2025)
Aircraft maintenance is a multifaceted process that requires highly skilled, qualified and experienced personnel. Effective maintenance processes optimise aircraft operational lifespan, minimise lifecycle costs and improve reliability by reducing the probability of unexpected maintenance events. The initial diagnostic phase relies on detailed visual inspections conducted by certified technicians. Following inspections, data assessment leads to the development of a comprehensive maintenance plan, along with the sourcing of necessary resources and spare parts. As the maintenance, repair and overhaul (MRO) sector transitions into the era of Industry 4.0, there is a growing emphasis on integrating data analytics and cyber-physical systems into maintenance practices. A key objective in this evolution is the adoption of robotic systems for inspection tasks. This shift requires the reconfiguration of formal inspection procedures to ensure compatibility with robotic operations. Moreover, it is critical to address the specific requirements of robotics and to incorporate smart hangar technologies that take advantage of real-time data to improve both efficiency and effectiveness in maintenance operations. This study provides a comprehensive review of the MRO landscape and maintenance checks, with a particular focus on robotic aircraft inspection systems, navigation and smart hangar infrastructure. The discussion concludes with an examination of defect detection methods using machine vision along with relevant metrics to compare with human performance.
Keywords: Aircraft Inspection; aircraft maintenance; automated diagnostics; hangar of the future; Industry 4.0; Industry 5.0; MRO; NDT; robotics; smart hangar; smart infrastructure; 40 Engineering; 9 Industry, Innovation and Infrastructure; Aerospace & Aeronautics; 35 Commerce, management, tourism and services